A Rab33b missense mouse model for Smith-McCort dysplasia shows bone resorption defects and altered protein glycosylation - Dimori, Milena; Pokrovskaya, Irina D.; Liu, Shijie; Sherrill, John T.; Gomez-Acevedo, Horacio; Fu, Qiang; Storrie, Brian; Lupashin, Vladimir V.; Morello, Roy (Frontiers in Genetics, 2023)
Smith McCort (SMC) dysplasia is a rare, autosomal recessive, osteochondrodysplasia that can be caused by pathogenic variants in either RAB33B or DYM genes. These genes codes for proteins that are located at the Golgi apparatus and have a role in intracellular vesicle trafficking. We generated mice that carry a Rab33b disease-causing variant, c.136A>C (p.Lys46Gln), which is identical to that of members from a consanguineous family diagnosed with SMC. In male mice at 4 months of age, the Rab33b variant caused a mild increase in trabecular bone thickness in the spine and femur and in femoral mid-shaft cortical thickness with a concomitant reduction of the femoral medullary area, suggesting a bone resorption defect. In spite of the increase in trabecular and cortical thickness, bone histomorphometry showed a 4-fold increase in osteoclast parameters in homozygous Rab33b mice suggesting a putative impairment in osteoclast function, while dynamic parameters of bone formation were similar in mutant versus control mice. Femur biomechanical tests showed an increased in yield load and a progressive elevation, from WT to heterozygote to homozygous mutants, of bone intrinsic properties. These findings suggest an overall impact on bone material properties which may be caused by disturbed protein glycosylation in cells contributing to skeletal formation, supported by the altered and variable pattern of lectin staining in murine and human tissue cultured cells and in liver and bone murine tissues. The mouse model only reproduced some of the features of the human disease and was sex-specific, manifesting in male but not female mice. Our data reveal a potential novel role of RAB33B in osteoclast function and protein glycosylation and their dysregulation in SMC and lay the foundation for future studies.